Covalently bonded polystyrene/SiO2 microspheres via emulsion polymerisation stabilised solely by surface active Pickering stabiliser. (1st May 2013) - Yin*, D Z; Du, X; Zhang, Q Y; Liu, H
<x xml:space="preserve">Abstract</x> Covalently bonded polystyrene/SiO2 microspheres were synthesised via Pickering emulsion polymerisation using methacryloxypropyltrimethoxysilane modified SiO2 as a sole stabiliser. The effect of polymerisation condition on morphologies of composites was investigated, and a formation mechanism of microspheres with different morphologies was proposed. Three strategies, increasing amount of stabiliser, adding inhibitor in continuous phase and employing cross-linking agent, were employed to regulate the morphology of products. It was concluded that suppression of nucleation in continuous phase was critical for the formation of dispersive microspheres with high sphericity and smooth surface.